(untitled) (Journal of Economic Research & Business Administration, 2019)
Actually, effective activity of enterprises, firms, agriculture production in economy depends how they can predict and forecasting the future. Activity forecasting of enterprises, firms means evaluation of their development which based on an analysis of market environment, changes. In market conditions , the role of forecasts increasing for managers of different levels. In that regard ,statistical forecasting methods have become important instrument for analytics, marketing activity. Currently, the range of forecasting tasks has expanded. Forecasting is the basis for making management decisions and improving the management process. The accuracy and reliability of the forecast results provides for the identification of the development of socio-economic systems, the study of the possibility of using existing resources and hidden reserves necessary to improve the efficiency of operation and future development. This article discusses the possibilities of using various modeling options for building final forecasts, as well as topical issues that often arise in forecasting and relating to determining the nature of seasonality, assessing the accuracy and adequacy of the constructed model. The article outlines the significance of trend-seasonal linear type models, based on a comparison of two alternative approaches to modeling price movements, reveals the adequacy of the application of a linear model based on chain price indices for milk. In turn, the separation of forecasting methods given in the study is rather arbitrary, since in practice they are interrelated and complementary. Any forecast estimate necessarily includes elements of extrapolation, modeling and expert opinion. However, for the conditions of operation of any entrepreneurial structure at present, which are characterized by environmental instability and uncertainty of the future, the most effective, in our opinion, forecasting method – the development of a linear model built on the basis of chain indices of milk prices, was identified.